Pharmacokinetics of oleracimine in rats by ultra-high-performance liquid chromatography - Gonglin Qu; Liang Xu; Wenjie Zhang; Xixiang Ying (Universidade de São Paulo, 2019)
The novel alkaloid, oleracimine, presented remarkable anti-inflammatory bioactivity, and therefore, its pharmacokinetics was investigated in rat plasma after intravenous and oral administration by using a rapid ultra-high-performance liquid chromatography (UHPLC) method with UV detection at 270 nm. The analysis was performed on a shim-pack ODS column (75 mm×2 mm, 1.6 µm particle size, Shimadzu, Japan) column using isocratic elution with a mobile phase consisting of methanol-water (62:38, v/v) within 3 min. The results indicated that oleracimine was rapidly distributed with Tmax for 11.7 min after oral administration, which presented the double-peak phenomenon in the pharmacokinetic profile with a higher oral absolute bioavailability of 55.1% ± 7.83%.